ABC-, VEN- AND FREQUENCY ANALYSIS OF TREATMENT OF ATRIAL FIBRILLATION IN OUTCOME PATIENTS - A. N. Korobeynikova; S. V. Malchikova (Фармакоэкономика, 2016)
Atrial fibrillation is a serious social and health problems, the most common arrhythmia in practice, leading to an increased risk of death, stroke, heart failure. The results of pharmacoeconomical studies allow to evaluate the quality of drug therapy for atrial fibrillation, find rational drug usage and identify ways to optimize the consumption of medications. The objective of investigation is to hold ABC-, VENand frequency analysis of atrial fibrillation in out-patients to assess their compliance with national and international recommendations. Materials and methods. To analyze the treatment of atrial fibrillation 98 outpatients with atrial fibrillation were randomly selected. Every patient appealed to the reception to the physician at least twice in 2013. The data was recorded in a special card, and then analyzed using ABC-, VENand frequency analysis. Results. For the treatment of patients with different forms of atrial fibrillation has been used 114 types of drugs to the INN. Patients received from 3 to 12 drugs. For the treatment of patient with atrial fibrillation it spends an average of 11245.2 rubles per patient, for the treatment of heart disease it spends 8379.51 rubles., that is about 74.5%. The study found that received data is satisfied modern recommendations. The results of frequency analysis showed that the most prescribed drugs are medications with proven efficacy to the quality and duration of life. Conclusions. Data analysis revealed that the percentage volume of drugs between the groups as a whole corresponds to the recommended distribution of drugs.